Renshen Baidu powder protects ulcerative colitis via inhibiting the PI3K/Akt/NF-κB signaling pathway - Zhen Ye; Yuzheng Li; Yingqi She; Mingquan Wu; Yu Hu; Kaihua Qin; Linzhen Li; Han Yu; Qian Zhao; Zhao Jin; Fating Lu; Qiaobo Ye (Frontiers Media S.A., 2022)
Ulcerative colitis is a chronic and relapsing inflammatory bowel disease without satisfactory therapy available recently. Renshen Baidu powder (RSBDP) is a classic Chinese medicinal formula used since Chinese Song dynasty and has been proven as an effective treatment of ulcerative colitis in clinics. However, the active ingredients and the molecular mechanism have not been fully disclosed. It is imperative to explore the active ingredients and the mechanism of RSBDP. In this study, the potential active components for ulcerative colitis treatment in RSBDP were determined and predicted in silicon, and its molecular mechanisms were also presented, in which the PI3K/Akt/NF-κB signaling pathway was recognized to be vital. Basically, the pharmacodynamics and mechanistic studies of RSBDP for ulcerative colitis were implemented on TNBS-induced experimental rats. The results showed that RSBDP could ameliorate the disease activity index and colon weight, as well as improve colonic shortening and colon histology. In addition, the tumor necrosis factor-α (TNF-α), diamine oxidase, intercellular adhesion molecule-1, and endotoxin in serum were also reduced. It is worth mentioning that the PI3K/Akt/NF-κB signaling pathway was inhibited after RSBDP administration via inhibiting the phosphorylation of proteins. In conclusion, RSBDP effectively ameliorates TNBS-induced colitis rats by inhibiting the PI3K/Akt/NF-κB signaling pathway.